Interventions to Minimize Medication Error by Nurses in Intensive Care: A Scoping Review Protocol - Fábio Coelho; Luís Furtado; Natália Mendonça; Hélia Soares; Hugo Duarte; Cristina Costeira; Cátia Santos; Joana Pereira Sousa (MDPI AG, 2023)
Medication errors represent a concern for healthcare organizations due to their negative consequences. In the nursing context, these errors represent a threat to the quality of care and patient safety. Many factors have been identified as potential causes for these errors in intensive care units. A scoping review will be developed to identify interventions/strategies to minimize the occurrence of medication errors by nurses, considering the Joanna Briggs Institute (JBI) methodology. A search will be conducted in the EbscoHost (CINAHL Complete and MEDLINE), Embase and PubMed databases. Data analysis, extraction and synthesis will be carried out by two reviewers independently. This review will attempt to map which interventions are more specific to minimizing medication error by nurses in intensive care and to recognize which factors influence this type of error to mitigate practices that may lead to error. This protocol acts as the framework for a scoping review in the strategy to map the interventions and which factors contribute to the medication error by intensive care nurses. This study was prospectively registered with the Open Science Framework on 21 April 2023 with registration number DOI 10.17605/OSF.IO/94KH3.